Implementasi Website Elektronik Analisis Beban Kerja (E-ABK) pada Kantor Kelurahan Bongkaran Kota Surabaya - Ratih Maulidiyah; Oktarizka Reviandani (IAI Nasional Laa Roiba Bogor, 2024)
Based on Article 56 Paragraph 1 of Constitution Number 5 of 2014 regarding State Civil Apparatus which states that each Government Agency has an obligation regarding the preparation of needs for types of positions and number of employees based on position analysis (Anjab) and workload analysis (ABK) in order to meet needs. The ideal organizational structure of Government Agencies in carrying out their main tasks and functions. This research looks at the problems at the preparation stage and the flow of problems in the filling process, the incompatibility of the uploaded supporting data of course affects the position requirements of existing employees. So the aim of this research is to find out the extent of the implementation of the 2024 Workload Analysis Information System (ABK) among Bongkaran Subdistrict Office employees, Surabaya. The method used in this research is a qualitative descriptive method. The informants in this research were the Secretary of Bongkaran Subdistrict and the Head of People's Welfare and Economic Affairs. Data collection techniques use interviews, observation and documentation. The research results showed that the procedure for using the 2024 Workload Analysis Information System (ABK) has not been running optimally and is less effective because there has been no outreach and training for members who run the application. It can be concluded that the implementation process has not been carried out well because it is hampered by human resources in Bongkaran Village, who still do not understand the correct format for working with crew member.